The Determinants of Customer Satisfaction at Bank Syariah Indonesia - Dwi Ayuk Indriawati; Edi Susilo (Mutanaqishah: Journal of Islamic Banking, 2025)
Purpose – This study aims to examine the effect of Islamic service quality, commitment, corporate image, and level of trust in shaping customer satisfaction at Bank Syariah Indonesia (BSI) KCP Jepara. Methodology – This study uses a quantitative approach involving 106 customers of Bank Syariah Indonesia (BSI) KCP Jepara as a sample. The sampling technique applied is convenience sampling, a non-probability sampling method. Data collection was carried out through questionnaires distributed online and directly. The data obtained were then analyzed using multiple linear regression, hypothesis testing (T and F), and classical assumption tests, which include normality, multicollinearity, heteroscedasticity, and the coefficient of determination, with the help of IBM SPSS 23 software. Findings – The study found that Islamic service quality and trust level have a positive and significant impact on customer satisfaction. However, commitment and corporate image did not show a significant influence on the level of satisfaction. Implications – The results of this study indicate that sharia-based services and the level of trust have an important role in increasing customer satisfaction. Therefore, BSI KCP Jepara is advised to continue to optimize the quality of Islamic services and maintain transparency and trust to maintain customer loyalty. Originality – This research presents a new perspective on the various factors that play a role in shaping customer satisfaction in Islamic banking, especially at BSI KCP Jepara. Different from some previous studies, this study found that commitment and corporate image are not always the dominant factors in shaping Islamic bank customer satisfaction.